2013
DOI: 10.1039/c3cp51813b
|View full text |Cite
|
Sign up to set email alerts
|

High performance thylakoid bio-solar cell using laccase enzymatic biocathodes

Abstract: Thylakoid membranes have previously been used for electrochemical solar energy conversion, but the current output and open circuit voltage are low, in part due to limitations of the cathode. In this paper, a thylakoid bioanode and laccase biocathode were combined in the construction of a bio-solar cell capable of light-induced generation of electrical power. This two-compartment cell showed a greater than 5-fold increase in short circuit current density and an open circuit voltage 0.275 V larger than that of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…The same bioanode electrodes were accordingly employed in two-compartment bio-solar cells 45 to further probe whether the amperometric trends hold and whether COEs improve (a) photocurrent generation within the thylakoids or (b) the thylakoid-electrode contact for current harvesting-or a combination of (a) and (b). An example of the obtained solar cell data is shown in Fig.…”
Section: Bio-solar Cell Experiments Reveal Statistically Significant mentioning
confidence: 99%
See 2 more Smart Citations
“…The same bioanode electrodes were accordingly employed in two-compartment bio-solar cells 45 to further probe whether the amperometric trends hold and whether COEs improve (a) photocurrent generation within the thylakoids or (b) the thylakoid-electrode contact for current harvesting-or a combination of (a) and (b). An example of the obtained solar cell data is shown in Fig.…”
Section: Bio-solar Cell Experiments Reveal Statistically Significant mentioning
confidence: 99%
“…Herein, immobilization is accomplished via silica encapsulation with catalase, 37 though thylakoid membranes may also be "wired" to osmium redox polymers, 38 suspended with gold nanoparticles and quinones, 39 frozen in an albumin matrix, 40 incorporated in electrochemical cells with various mediators, 41 or tethered to multiwalled carbon nanotubes (MWCNTs). 45,46 The thylakoid active layer absorbs light and generates electrons that are harvested as anodic photocurrent. 43,44 Two-compartment bio-solar cells constructed from spinach thylakoid bioanodes and laccase biocathodes were recently reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical applications are increasingly exploiting the efficiency of photosynthesis for solid-state devices mimicking photovoltaic cells. Photo-electric currents have been achieved with immobilized chloroplasts [7], thylakoid membranes [8-10], PSII [11, 12] or PSI [13-16] core complexes and isolated reaction centres [17-19]. One of the most promising current bio-photovoltaic without using elaborate or expensive surface chemistries is a PSI complex attached to a semiconductor, achieving a photocurrent density of 362 µA/cm 2 and 0.5 V [15].…”
Section: Introductionmentioning
confidence: 99%
“…29 Their thylakoid bioanode was able to generate 2.46 μA/cm 2 when connected with a Pt air-breathing cathode 29 and 14.0 μA/cm 2 with a laccase oxygen reduction biocathode. 49 The OCVs for these cells were 0.46 V and 0.73 V, respectively. They also showed that this system could be used as a self-powered herbicide biosensor which allows for the determination of herbicide in solution based on the decrease in power output when the photobioelectrocatalysis is inhibited, 50 and the different sources of thylakoids have different sensitivities for herbicide detection.…”
Section: Thylakoidsmentioning
confidence: 99%